Pilot Study of Visual and Quantitative Image Analysis of Facial Surface Asymmetry in Unilateral Complete Cleft Lip and Palate. (August 2019) - Kimura, Namiko; Kim, Hyoungseop; Okawachi, Takako; Fuchigami, Takao; Tezuka, Masahiro; Kibe, Toshiro; Amir, Muhammad Subhan; Inada, Emi; Ishihata, Kiyohide; Nozoe, Etsuro; Nakamura, Norifumi
Objective: To visualize and quantitatively analyze facial surface asymmetry following primary cleft lip repair in patients with unilateral cleft lip and palate (UCLP) and to compare this with noncleft controls. Design: Retrospective comparative study. Patients: Twenty-two patients with complete UCLP who underwent primary lip repair from 2009 to 2013 were enrolled in this study. The preserved 3-dimensional (3D) data of 23 healthy Japanese participants with the same age were used as controls. Interventions: All patients had received primary labioplasty in accordance with Cronin triangular flap method with orbicular oris muscle reconstruction. Main Outcome Measures: Shadow and zebra images established from moiré images, which were reconstructed from 3D facial data using stereophotogrammetry, were bisected and reversed by the symmetry axes (the middle line of the face). The discrepancies of the gravity and density between cleft and noncleft sides in 2 regions of interest, facial and lip areas, were then calculated and compared with those of healthy participants. Results: In the UCLP group, the mean discrepancies of gravity on shadow and zebra images were 1.76 ± 0.70 and 2.63 ± 1.72 pixels, respectively, in the facial area and 1.31 ± 0.36 and 3.83 ± 2.08 pixels, respectively, in the lip area. There was a significant difference in the mean discrepancies of gravity and density on zebra images in the lip area between the UCLP and control groups. Conclusions: Our image analysis of digital facial surface asymmetry in patients with UCLP provides visual and quantitative information, and it may contribute to improvements in muscle reconstruction on cleft lip repair.